Dynamic contrast enhanced magnetic resonance lymphangiography: Categorization of imaging findings and correlation with patient management. Issue 101 (April 2018) - Pimpalwar, Sheena; Chinnadurai, Ponraj; Chau, Alex; Pereyra, Mercedes; Ashton, Daniel; Masand, Prakash; Krishnamurthy, Rajesh; Jadhav, Siddharth
Abstract: Objective: To review the technical aspects and categorize the imaging findings of dynamic contrast enhanced magnetic resonance lymphangiography (DCMRL) and correlate the findings with patient management options. Materials and methods: A retrospective review of patients who underwent DCMRL between June 2012 and August 2017 at a tertiary care paediatric hospital was performed. Twenty-five DCMRL studies were performed in 23 patients (9 males, 13 females, 1 ambiguous gender) with a median age of 4 years (range: 1 month–29 years). DCMRL imaging findings were reviewed, categorized and the impact on patient management was studied. Results: DCMRL was technically successful in 23/25 (92%) studies. DCMRL findings were categorized based on the status of central conducting lymphatics (CCL) and alternate lymphatic pathways as follows: Type 1 – normal CCL with no alternate lymphatic pathways, Type 2 – partial ( 2a ) or complete ( 2b ) non-visualization of CCL with reflux of contrast into alternate pathways and Type 3 – normal CCL with additional filling of alternate pathways. Type 1 DCMRL patients (n = 5) were reassured and conservative management was continued, Type 2 patients (n = 10) had evidence of CCL obstruction hence thoracic duct ligation or embolization was avoided and other options such as lymphatic fluid diversion using Denver ® shunt or lympho-venous anastomosis were used, and Type 3 patients (n = 8) were evaluated for elevated central venous pressure as a cause of lymphatic backflow in addition to Denver ® shunt, lympho-venous anastomosis, thoracic duct ligation or embolization. Conclusion: DCMRL is an evolving imaging technique for understanding abnormalities of the central conducting lymphatics. Categorization of imaging findings may be helpful in guiding selection of management options.